Synthesis and Modeling of Adsorbents from Natural Materials for Heavy Metal Lead in Mahakam River Water Samples - Rahmawati Munir; Ahmad Zarkasi; Dadan Hamdani; Sahara Hamas Intifadhah; Akbar Perdana; Alris Sanca Pratama Putra (Lambung Mangkurat University Press, 2023)
The Mahakam River is a source of water for the people of Samarinda, East Kalimantan. However, Mahakam river water is not classified as quality water. As a result of industrial mining activities, river water is polluted by heavy metals such as Lead (Pb). These problems can be overcome by using the adsorption method to purify water. The adsorption method has become popular in adsorbing heavy metals contained in polluted water. The purpose of this study was to synthesize natural materials which are adsorbents for the heavy metal Pb. The materials used as natural adsorbents are household waste, namely ashes (AG), egg shells (CT), tea dregs (AT). Based on the results of the Atomic Absorption Spectroscopy (AAS) characterization test, data were obtained on the decrease in the concentration of heavy metal Pb in samples of Mahakam river water. The initial concentration of 1.8 mg/L became 0.24 mg/L (10 gr adsorbent AG) and became 0.17 mg/L (10 gr adsorbent AG+CT). While the use of AT adsorbent was applied to artificial waste with an initial concentration of 40 mg/L to 0.002 mg/L. Furthermore, according to data measurement, modeling was carried out using the Langmuir Isotherm and Freundlich Isotherm models to determine the adsorption capacity of tea dregs, eggshells, and ashes.